Особливості флейтових текстів Йоганна Себастьяна Баха - Карпяк, А. (Студії мистецтвознавчі, 2007)
The article highlights the issues relating to the counterbalance of sounding, the specifics of the timbre, register incompatibility, etc. which can be commonly observed among flutists working on the output of J.S. Bach. Disnegard for the above-mentioned details can cause a decisive negative influence on the performance through the neglect of traditional standarts and conditions of performance.